2010
DOI: 10.3171/2010.1.jns091296
|View full text |Cite
|
Sign up to set email alerts
|

Selection of patients with idiopathic normal-pressure hydrocephalus for shunt placement: a single-institution experience

Abstract: Our strategy based on the analysis of CSF pulse pressure parameters seems to have a great accuracy in predicting surgical outcome in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 42 publications
0
38
0
1
Order By: Relevance
“…Previously investigated parameters which describe aspects of CSF dynamics similar to the pulsatility curve include the RAP Index21 (an index of cerebrospinal compensatory reserve) and the Elastance Index 34. The Elastance Index, which is similar to RPPC but uses diastolic pressure rather than mean ICP, has shown good predictive results for INPH in a previous study34 but RPPC did not predict gait improvement in this study.…”
Section: Discussionmentioning
confidence: 52%
“…Previously investigated parameters which describe aspects of CSF dynamics similar to the pulsatility curve include the RAP Index21 (an index of cerebrospinal compensatory reserve) and the Elastance Index 34. The Elastance Index, which is similar to RPPC but uses diastolic pressure rather than mean ICP, has shown good predictive results for INPH in a previous study34 but RPPC did not predict gait improvement in this study.…”
Section: Discussionmentioning
confidence: 52%
“…An elevated outflow resistance has been shown to have prognostic power for selecting shunt responders (Boon et al 1997), but there are also studies showing a lack of prognostic power (Malm et al 1995). Similarly, one study (Anile et al 2010) showed a good prognostic power for a high intracranial elastance (IE) slope, which is closely related to RPPC, while another study demonstrated a lack of prognostic power for the slope of pulsation amplitude versus pressure (Delwel et al 2005).…”
Section: Predictive Testsmentioning
confidence: 99%
“…More recently suggested prognostic tests often focus on parameters describing the cardiac-related pulsations in ICP or CSF flow. [5,10,17,31,33] So far no consensus on the most appropriate test has been reached, and the interaction of different CSF dynamic parameters complicates the effort of identifying the key aspect of the CSF dynamic disturbance. One test with promising results is based on the mean pulse amplitude of cardiacrelated ICP pulsations (AMPmean) during 10 minutes of constant flow infusion.…”
Section: Introductionmentioning
confidence: 99%